Mongolia : 2011 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2011)
The economy of Mongolia was extremely affected during the crisis, owing to its dependency on mineral exports and history of procyclical macroeconomic policies. In this study, the ex post evaluation (EPE) of Mongolia's experience is reviewed. The EPE focused on program design and implementation. Progress toward strengthening financial oversight and implementation of a financial sector assessment program are discussed. Deposit insurance was established to replace the blanket deposit guarantee. Structural reforms have improved. Finally, the authorities' intention to remain engaged with the IMF under post-program monitoring is outlined.